Application of supercritical water for green recycling of epoxy-based carbon fiber reinforced plastic. (22nd March 2019) - Kim, Young Nam; Kim, Young-O.; Kim, Seong Yun; Park, Min; Yang, Beomjoo; Kim, Jaewoo; Jung, Yong Chae
Abstract: The objective of this study is to fabricate conductive carbon fiber composites with thermal and electrical properties by degradation carbon-fiber-reinforced plastics (CFRPs) and recycled carbon fibers using only supercritical water without any catalyst or oxidant. We focused on a recycling method that is harmless to the human body and environment-friendly, by using supercritical fluid water rather than recycling CFRP by physical or pyrolysis methods. In particular, we recycled carbon fibers (R-CFs) in which up to 99.5% of epoxy resin was removed, by optimizing the conditions of supercritical fluid water (SCF-W) treatment, and we fabricated conductive R-CFs composites with thermal and electrical properties by combining the R-CFs with cyclic butylene terephthalate (CBT), which is a polymerizable low-viscosity thermoplastic resin. The fabricated composites had a thermal conductivity of 1.35 ± 0.05 (W/mK) and an electrical conductivity of 11.23 × 10 −6 (S/cm) when the added amount of recycled carbon fibers was 5 wt%. Graphical abstract: Image 1